Pengembangan Generasi Sehat Melalui Edukasi dan Implementasi Program Sanitasi serta Pola Hidup Sehat di MI Annidham Jember - Ubaidillah, Mohammad; Sukaesih, Nabilah Shintia; Nur, Sefi Anindia Tiyana; Putri, Aulia Meuthia; Putra, Iqbal Firlana; Saputra, Martha Alit; Ramadhani, Vian; Puspito, Agung Nugroho (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This social project aims to enhance students' knowledge and awareness of the importance of environmental sanitation and healthy lifestyles. Additionally, it seeks to modify their behavior by implementing sanitation and healthy living practices in their daily routines, such as regular handwashing, cleaning the classroom, and disposing of waste properly. The community service was carried out at MI Annidham, Sumbersari District, Jember Regency, with a total of 44 students from grades 3 and 4. The method employed was a conventional interactive approach, involving presentations, practice sessions, Q&A, and discussions during the implementation. The results of the community service indicate a 60% increase in students' knowledge and understanding of sanitation, hygiene, and clean and healthy lifestyle practices, which were the main topics addressed in the service activities. Furthermore, students' participation in this activity demonstrated high enthusiasm and a strong eagerness to learn, positively impacting their knowledge and skills.